Development of expanded polystyrene cushion design guidelines for reliable flat-screen television packaging - Kassim, Normah (2020)
The packaging is a method used to protect products from damage that involves input from a variety of disciplines like engineering, sciences, economics, and packaging design knowledge including the home appliances products. Therefore, this study is mainly to produce the EPS cushion design guidelines for flat-screen television packaging. Further, to increase the effectiveness of EPS cushion packaging reliability, also to decrease the cost and time of EPS cushion packaging development. This research is comprehensively studying on a packaging design by using quantitative and qualitative methods; EPS cushion design validation by comparing the results between destructive testing and finite element analysis using ANSYS software, also reverse engineering analysis about the existing EPS cushion packaging design and process. Meanwhile, the simulation analysis results have been effectively proven that it can be used for the prediction of a possible defect or the design weakness of EPS cushion through clamping test, limit drop test, and drop test. So, these methods preciously effective to identify the major factors in designing EPS cushions design, especially flat-screen television packaging. As a result, found that are five types of factors need to be considered in the designing process of EPS cushion packaging’s, such as rib positioning, layout of packaging, and thickness. Besides that, also found that finite element analysis is an effective method to be used and implemented especially in the manufacturing industry to enhance the television packaging design reliability. Moreover, the design guideline provides achievement in terms of cost and time reduction as well the packaging development process is improved.